Experimental study of heat-killed oocysts of Cryptosporidium Parvum in Balb/ c Mice - Mohammed Khudhair; Nabeel Al-Niaeemi (College of Education for Pure Sciences, 2020)
The present study investigated the possibility of infecting Mus musculus mice, experimentally, with cryptosporidiosis by inoculation with Cryptosporidium parvum oocysts, after treatment with temperatures (70 °C) and non-treated oocysts, single or double doses, aiming at enrichment of information related to existence of oocysts infected, outside the body of the host when subjected to temperatures. Criteria taken into consideration are the period spent by the parasite inside the body of the host, number of oocytes shed by the parasite with the host's stool, total and differential leukocyte count. The Results of the present study shows: 1-      Shedding of Oocysts started at the 4th day post infection by non-treated Oocysts, at single dose, and continued until the day 35 post infection, whereas with the challenge dose it continued until the 17th day  post infection. 2-      Temperature at (70Co) killed the Oocysts as infection of mice didn't occur. 3-      Generally, a gradual increase in total and differential leukocyte count on infection with non-treated Oocysts at day 3 post infection.